DESIGN AND IMPLEMENTATION OF A METAVERSE-BASED PLATFORM FOR THEMATIC TOURISM VILLAGES - Aditya, Addin; Kurniawan, Rahmat; Maulana, Fatih; Darwanza, Muhammad Alif Nur (Informatika, Universitas Jenderal Soedirman, 2025)
This research investigates the integration of metaverse technology into the design of thematic tourism villages to address the declining appeal of such destinations and the limited adoption of digital tools for promotion and education. Using the Kayutangan Heritage Village in Malang as a case study, the study employs a Design Thinking approach to identify challenges, ideate solutions, and develop a metaverse-based platform prototype. This platform leverages immersive 3D environments to enable users to explore cultural heritage and historical narratives in a virtual context. The findings highlight the platform's ability to create resilient, engaging, and educational tourism experiences that attract diverse audiences while supporting local economies. By offering innovative, interactive ways to connect with cultural heritage, the metaverse platform demonstrates its potential as a transformative tool for digital tourism. The research contributes to the broader discourse on sustainable tourism by showcasing the metaverse’s role in preserving cultural heritage and enhancing digital connectivity. Its impact is evident in fostering a deeper understanding of cultural assets and promoting digital tourism innovations that align with contemporary market demands, thus paving the way for the widespread adoption of metaverse technology in similar contexts.